Sustainable design from vision to action - Faludi, Jeremy (Routledge, 2025)
"This book offers a comprehensive guide to the sustainable design of products, services, or related systems. It goes beyond concept explanations to provide you with practical instructions on how to apply the tools and methods to your own designs. The world is finally waking up to the necessity of sustainability, especially in the design and engineering of all the physical products we spend every day surrounded by. This innovative textbook not only provides a thorough understanding of the high-level values and goals of sustainable design, but also gives readers actionable step-by-step guides for how to implement them on the ground, in daily practice. This includes quick reference tables and other resources for practical design, with lists of sources for greater depth. The activities can be used by designers and engineers, in classrooms, or in industry. The book focuses primarily on physical product development, but also applies to services, systems, and digital products. It includes a thorough range of quantitative and qualitative methods across the whole product life cycle, including material choice, energy use, systems thinking, design for recycling, user behavior change, business models, equity and inclusion, and more. The book aims to change your design practice to help build a world that is healthy, abundant, beautiful, and fulfilling for all species, for all time. This highly illustrated text will provide an excellent introduction to sustainable design in practice for industrial design and mechanical engineering students. It will also be useful for professional designers, engineers, and managers in industry"-- Provided by publisher.
Keywords: Industrial design.; Sustainable design.; elektronické knihy; electronic books